2007
DOI: 10.1089/ten.2006.0271
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells Associated with Macroporous Bioceramics for Long Bone Repair: 6- to 7-Year Outcome of a Pilot Clinical Study

Abstract: Extensive bone loss is still a major problem in orthopedics. A number of different therapeutic approaches have been developed and proposed, but so far none have proven to be fully satisfactory. We used a new tissue engineering approach to treat four patients with large bone diaphysis defects and poor therapeutic alternatives. To obtain implantable three-dimensional (3D) living constructs, cells isolated from the patients' bone marrow stroma were expanded in culture and seeded onto porous hydroxyapatite (HA) ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
350
0
14

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 527 publications
(370 citation statements)
references
References 51 publications
6
350
0
14
Order By: Relevance
“…This could be the reason behind the increased soft and hard tissue formation around the implants loaded with BM compared to those without BM. Similarly to previous research, our study revealed that the combination of bioceramic implants with BM substantially increased the amount of bone growing on the outer implant surface (Kon et al, 2000;Marcacci et al, 2007). Interestingly, even though different amounts of bone grew on the outer surface of all the implants, no bone formation occurred within the inner compartment of any of the implants tested.…”
Section: Oxygen Delivery In Vitrosupporting
confidence: 88%
“…This could be the reason behind the increased soft and hard tissue formation around the implants loaded with BM compared to those without BM. Similarly to previous research, our study revealed that the combination of bioceramic implants with BM substantially increased the amount of bone growing on the outer implant surface (Kon et al, 2000;Marcacci et al, 2007). Interestingly, even though different amounts of bone grew on the outer surface of all the implants, no bone formation occurred within the inner compartment of any of the implants tested.…”
Section: Oxygen Delivery In Vitrosupporting
confidence: 88%
“…These osteoconductive scaffolds are often combined with growth factors (osteoinductive) (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and/or with cells (osteogenic) (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) to induce active stimulation of bone regeneration. The objective of most of these investigations is to enable bone defect healing, which remains an unsolved clinical problem.…”
mentioning
confidence: 99%
“…According to the diamond concept [12,[124][125][126][127], the biological elements of these therapies should involve MSCs and growth mediators including those promoting the new vasculature formation. Whether MSCs are delivered within concentrated or not-concentrated mononuclear bone marrow cells [128,129] or as culture-expanded pure population and loaded on matrices [130] or injected subcutaneously [131], their therapeutic use still needs further optimisation. The inflammation status could affect considerably the effectiveness of the regenerative treatments at least in part via their effect on MSCs [132].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%